ADULT SECOND LANGUAGE ACQUISITION IN CROSS CULTURAL CONTEXT: A CASE STUDY OF A STUDENT FROM GUINEA BISSAU (WEST AFRICA) WHO LEARNS BAHASA INDONESIA AS HIS SECOND LANGUAGE - Tonga, Umbu; Hafid, Hilda (Elite : English and Literature Journal, 2019)
The world migration is an interesting issue to be discussed. Reflecting on the recent phenomenon, world migration makes the people become the world citizen. Indeed, it is challenging the people to be more aware of cross cultural understanding because they have to live in a place where the culture is totally different from theirs. One key to face the challenges of becoming world citizen is to be able to communicate with a lingua franca used in a specific setting. This study aims to investigate how a student from Guinea Bissau (West Africa) learns Bahasa Indonesia as his second language when he studies in Indonesia. This study was conducted by doing an in-depth interview with the subject used notes and video recording. The results show the relevant influence of first language to his second language acquisition and the settings of language learning exposed the subject to effectively communicate in L2 and also gets corrective feedbacks when he makes grammatical mistakes or errors. Keywords: World Migration, Cross Cultural Understanding, Second Language Acquisition ABSTRAK Migrasi dunia merupakan suatu isu yang menarik untuk didiskusikan. Berkaca dari fenomena masa kini, migrasi dunia membuat manusia menjadi warga negara dunia. Tentu saja, hal ini menantang manusia untuk semakin menyadari pemahaman lintas budaya karena mereka hidup di tempat di mana budayanya sangat berbeda dari budaya asal mereka. Salah satu kunci untuk menghadapi tantangan menjadi warga negara dunia adalah mampu berkomunikasi dengan bahasa pengantar yang digunakan di tempat tertentu. Studi ini bertujuan untuk menginvestigasi bagaimana seorang mahasiswa dari Guinea Bissau (Afrika Barat) mempelajari Bahasa Indonesia sebagai bahasa keduanya ketika dia melanjutkan studi di Indonesia. Studi ini dilakukan melalui wawancara mendalam dengan subyek, menggunakan catatan dan rekaman video. Hasilnya menunjukan pengaruh relevan dari bahasa pertamanya terhadap pemerolehan bahasa keduanya dan tempat pembelajaran bahasa mengarahkan subyek untuk berkomunikasi secara efektif dalam bahasa kedua dan juga subyek mendapatkan masukan yang mengoreksi ketika dia membuat kesalahan gramatikal. Keywords: Migrasi Dunia, Pemahaman Lintas Budaya, Pemerolehan Bahasa Kedua